On the Comparative Fishing Experiments with a Four Seam and a Two Seam on the East Coast - Satyanarayana, A. V. V.; Narayanappa, G.; Raju, D. A. Narasimha (Fishery Technology, 1972)
Fishing experiments were undertaken to study the relative utility of a newly designed four seam type net on a conventional two seam net at the centre along the East Coast in both inshore and deeper zones (upto 100m) and the results indicated that the new four seam net has given higher catch rate of 6 to 8% more with higher catch rate of fish supposed to belong to off bottom region. Further this gear found more selective in obtaining Lactarius, which is one of the good variety of fish from trawlers, in both quantity as well as in quality. In terms of horizontal spread this new net gave less on comparison with the conventional two seam net, thereby showed corresponding increase in vertical spread; but warp tension remained more or less same in both the gear. Both gear have worked equally well in majority of depth ranges experimented with optimum spread. Finally the results indicated that the new net can work well from the present trawlers along the coast.